2023
DOI: 10.1186/s13046-023-02827-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT1 facilitates the progression of gastric cancer via PTBP1-mediated glycolysis enhancement

Cong Zhang,
Huixia Wang,
Qingwei Liu
et al.

Abstract: Background Gastric cancer (GC) is one of the most prevalent malignant tumors of the digestive system. As a hallmark of cancer, energy-related metabolic reprogramming is manipulated by multiple factors, including long non-coding RNAs (lncRNAs). Notably, lncRNA CCAT1 has been identified as a crucial regulator in tumor progression. Nevertheless, the precise molecular mechanisms underlying the involvement of CCAT1 in metabolic reprogramming of GC remain unclear. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The lncRNA colon cancer-associated transcript-1 (CCAT1), firstly identified in CRC [ 148 ], is increased expressing in GC cells and participates in promoting the malignant progression of GC through enhancing autophagy [ 149 ]. Zhang et al presented new evidence indicating that the expression of lncRNA CCAT1 was also significantly elevated in the tissues and plasma exosomes of patients with GC; moreover, lncRNA CCAT1 was confirmed to interact directly with polypyrimidine tract binding protein 1 (PTBP1) and effectively maintain its stability by inhibiting the ubiquitin-mediated degradation process, thus to facilitate the transition from PKM1 to PKM2 to augment glycolysis in GC cells [ 150 ]. It is worthy of note that the reprogrammed Warburg effect can in turn regulate many hallmarks of cancer through promoting the release of exosome by cancer cells [ 151 , 152 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…The lncRNA colon cancer-associated transcript-1 (CCAT1), firstly identified in CRC [ 148 ], is increased expressing in GC cells and participates in promoting the malignant progression of GC through enhancing autophagy [ 149 ]. Zhang et al presented new evidence indicating that the expression of lncRNA CCAT1 was also significantly elevated in the tissues and plasma exosomes of patients with GC; moreover, lncRNA CCAT1 was confirmed to interact directly with polypyrimidine tract binding protein 1 (PTBP1) and effectively maintain its stability by inhibiting the ubiquitin-mediated degradation process, thus to facilitate the transition from PKM1 to PKM2 to augment glycolysis in GC cells [ 150 ]. It is worthy of note that the reprogrammed Warburg effect can in turn regulate many hallmarks of cancer through promoting the release of exosome by cancer cells [ 151 , 152 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…(II) As transcriptional regulators, lncRNAs can bind to downstream gene promoters ( 36 ), transcription factors ( 37 , 38 ), or recruit complexes to regulate gene expression patterns ( 39 ). (III) At the post-transcriptional level, lncRNAs interact with splicing factors to splice precursor mRNAs ( 40 ), combine with RNA-binding protein and affect mRNA stability ( 41 , 42 ), and bind to proteins or mRNAs and impact their biological functions ( 43 , 44 ). (IV) LncRNA acting as microRNAs (miRNAs) sponges to regulate the expression of their targets ( 45 , 46 ).…”
Section: Overview Of Lncrnamentioning
confidence: 99%
“…Colon-cancer-associated transcript-1 (CCAT1), located at chromosomal region 8q24.21, is significantly upregulated in multiple types of cancer [ 57 , 58 , 59 , 60 , 61 ] and is also highly expressed in ESCC. Zhang et al demonstrated that knockdown of CCAT1 significantly suppressed cell migration in vivo and in vitro.…”
Section: Lncrnas Participate In the Process Of Ec Metastasismentioning
confidence: 99%